Clinical Characteristics of SARS-CoV-2 Acute Pulmonary Embolism and Adjusted D-dimer for Emergency Department Patients - Iltifat Husain; James C. O’Neill; Jacob H. Schoeneck; K. Alexander Soltany; Hollins Clark; Erika Weidman Rice; Alex Gross; Jonathan Redding; David M. Cline (Western Journal of Emergency Medicine, 2023)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and acute pulmonary embolism (APE) present a diagnostic challenge in the emergency department (ED) setting. We aimed to identify key clinical characteristics and D-dimer thresholds associated with APE in SARS-CoV-2 positive ED patients. Methods: We performed a multicenter, retrospective cohort study for adult patients who were diagnosed with coronavirus 2019 (COVID-19) and had computed tomography pulmonary angiogram (CTPA) performed between March 17, 2020–January 31, 2021. We performed univariate analysis to determine numeric medians, chi-square values for association between clinical characteristic and positive CTPA. Logistic regression was used to determine the odds of a clinical characteristic being associated with a diagnosis of APE. Results: Of 408 patients who underwent CTPA, 29 (7.1%) were ultimately found to have APE. In multivariable analysis, patients with a body mass index greater than 32 (odds ratio [OR] 4.4, 95% confidence interval [CI] 1.0 -19.3), a heart rate greater than 90 beats per minute (bpm) (OR 5.0, 95% CI 1.0-24.9), and a D-dimer greater than 1,500 micrograms per liter (μg/L) (OR 5.6, 95% CI 1.6-20.2) were significantly associated with pulmonary embolism. In our population that received a D-dimer and was SARS-CoV-2 positive, limiting CTPA to patients with a heart rate over 90 or a D-dimer value over 1500 μg/L would reduce testing 27.2% and not miss APE. Conclusion: In patients with acute COVID-19 infections, D-dimer at standard cutoffs was not usable. Limiting CTPA using a combination of heart rate greater than 90 bpm or D-dimer greater than 1,500 μg/L would significantly decrease imaging in this population.